2015
DOI: 10.1167/tvst.4.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Topical Ocular Drug Delivery to the Back of the Eye by Mucus-Penetrating Particles

Abstract: These preclinical data support using MPP technology to engineer topical formulations to deliver therapeutic drug levels to the back of the eye and could provide major advancements in managing sight-threatening diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 44 publications
4
74
0
Order By: Relevance
“…They attributed this decrease to the reduction of mucoadhesive forces between the PLA-PEG NPs and the surface of the eye [174]. However, other more recent work by Schopf and coworkers suggested that nanoparticles coated with a dense, mucoinert PEG surface coating provided increased loteprednol etabonate (LE) delivery to the cornea and retina when applied topically to the surface of the rabbit eye compared to nanoparticles without a mucoinert PEG surface coating [176]. However, the mucoinert surface coating only led to improved LE delivery for nanoparticles (240 nm) and not microparticles (> 1 µm), suggesting that the nanoparticles (LE-MPP) were able to penetrate into the membrane-bound mucus layer of the eye, providing increased residence time and improved drug delivery.…”
Section: Non-systemic Applications For Improved Delivery With Pegymentioning
confidence: 99%
“…They attributed this decrease to the reduction of mucoadhesive forces between the PLA-PEG NPs and the surface of the eye [174]. However, other more recent work by Schopf and coworkers suggested that nanoparticles coated with a dense, mucoinert PEG surface coating provided increased loteprednol etabonate (LE) delivery to the cornea and retina when applied topically to the surface of the rabbit eye compared to nanoparticles without a mucoinert PEG surface coating [176]. However, the mucoinert surface coating only led to improved LE delivery for nanoparticles (240 nm) and not microparticles (> 1 µm), suggesting that the nanoparticles (LE-MPP) were able to penetrate into the membrane-bound mucus layer of the eye, providing increased residence time and improved drug delivery.…”
Section: Non-systemic Applications For Improved Delivery With Pegymentioning
confidence: 99%
“…[42,43] In particular, topical administration is inefficient in delivering medications to the posterior segment because of the rapid drainage through the nasolacrimal ducts, [44] as discussed in section 2.1.1. To reach the posterior segment of the eye, a topically administered drug must penetrate through the cornea (Figure 1), which represents a barrier from external agents that naturally serves to hinder the transport of either exogenous substances from the pre-corneal pockets.…”
Section: Routes Of Ocular Administrationmentioning
confidence: 99%
“…Delivery of drugs to the posterior segment of the eye through oral/parenteral routes is highly challenging because of the expression of blood ocular barriers. Topical administration is promising in terms of safety and patient compliance but the delivery of therapeutic agents to the posterior ocular tissues through this route is also an extremely difficult task (3, 4). Although various technological advances enhanced drug delivery into the front-of-the eye, back-of-the eye delivery through the topical route needs innovative strategies to improve pre-corneal residence and trans-ocular permeation characteristics of drug molecules (5, 6).…”
Section: Introductionmentioning
confidence: 99%